The Use of Google Meet for Critical Reading Improvement Strategies - Gunaldi Masbiran; Yeni Afriyeni (Universitas Pahlawan Tuanku Tambusai, 2021)
As we know that one of the most important aspect in mastering a language is the ability to read. As a matter of fact, that many students get low score in reading class lesson. On the other hand, only few students get high score in reading class lesson. If we analyze by using the four competencies of mastering english such as: Speaking, Writing, Reading and Listening, they have tight relationship each other. In the researcher point of view, based on daily observation and interview with some students, the main cause of students’ low reading achievement is reading strategy or techniques of reading. It can be checked in class activity, some of them do not have self confidence in reading and do the exercises. Thus, some of them do not do the assignment well, this can be caused by lack of knowledge of reading techniques and they also regard that reading is one the most difficult subject and bored to read english reading material. Consequently, they often get low marks in reading subject at the end of the the semester.